Ascetical and mystical experience in Chinese Buddhism - Dabetić Ilija (Kom: Časopis za Religijske Nauke)
The oldest religious beliefs of the ancient China were characterized by personification of natural phenomena, cult of ancestors with a developed magical element and frequent practice of alchemical experimentation. Sorcery continues to exist in later ages, as a feature of classical Chinese autochthonous religions, especially Daoist mystical efforts. In the period from the fourth to the second century before Christ, the presence of a sorcerer named "fangshi" (the way of the immortal - "Fangxiang dao") at the royal society was an established custom. The main idea of those spells was searching for ways that would provide man with eternal life. The historical momentum of meeting Chinese tradition with Buddhism could be noticed as one of the most significant events for the cultural history in this part of the world. The Buddhist teachings that reached Chinese people were quite different from the original apathetic and transtheistic ideology of Prince Siddhartha. The interpretation of Buddhism that appeared in China was religious Mahayana, which was open to mystical spirituality. The permeation of indigenous Chinese and newly arrived religious patterns will lead to the emergence of an unusual authentic form of ascetism and mysticism in religious life of the Far East. The discipline of pre-Buddhist Chinese religious devotees will influence the abundance and importance of the monastic community in Chinese Buddhism.